Evaluation Model and Empirical Analysis of the Graduate Mentor-Student Relationships from the Perspective of Academic Norms - Zhang, Chuan; Bo Zhang; Zhao, Zheng (Ilmu Inovasi Nusantara, 2025)
The rising incidence of academic misconduct has led to a heightened emphasis on academic norms. Consequently, the graduate mentor-student relationship, when viewed through the lens of academic norms, has emerged as a pivotal research topic in educational studies. This paper presents a logical association analysis between academic norms and the mentor-student relationship. It delineates the mentor-student dynamic into four distinct categories based on two core dimensions: academic cultivation and moral cultivation. An evaluative model and a range of indicator weights related to the mentor-student relationship from an academic norm perspective are established. This involves 15 level 2 indicators and 51 level 3 indicators, selected from 5 domains: quality of academic guidance, academic integrity cultivation, academic exchange and interaction, output of academic achievements, and students' academic growth. Empirical analysis is executed using data sourced from scholars' assignments and scores derived from the Likert five-point scale. The findings reveal that the weights assigned to academic integrity cultivation and quality of academic guidance, within the evaluation system for the mentor-student relationship, surpass 25%, indicating their significant influence. Notably, the